2014
DOI: 10.1074/mcp.o113.027870
|View full text |Cite
|
Sign up to set email alerts
|

Immunoaffinity Enrichment and Mass Spectrometry Analysis of Protein Methylation

Abstract: Protein methylation is a common posttranslational modification that mostly occurs on arginine and lysine residues. Arginine methylation has been reported to regulate RNA processing, gene transcription, DNA damage repair, protein translocation, and signal transduction. Lysine methylation is best known to regulate histone function and is involved in epigenetic regulation of gene transcription. To better study protein methylation, we have developed highly specific antibodies against monomethyl arginine; asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
446
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(479 citation statements)
references
References 60 publications
22
446
3
Order By: Relevance
“…The top five protein categories for Rme were receptor/channel/transporter/cell surface protein, RNA processing, transcriptional regulator, adhesion/extracellular protein, and adaptor/scaffold. A large number of unique Rme sites was identified from various heterogeneous nuclear ribonucleoprotein (hnRNP) isoforms, most of which have been identified before in a previous study (14). The presence of these posttranslationally modified hnRNP peptides in serum/plasma has not been previously reported.…”
Section: Enrichment Workflow For Ptm Peptide Identification-tomentioning
confidence: 81%
See 2 more Smart Citations
“…The top five protein categories for Rme were receptor/channel/transporter/cell surface protein, RNA processing, transcriptional regulator, adhesion/extracellular protein, and adaptor/scaffold. A large number of unique Rme sites was identified from various heterogeneous nuclear ribonucleoprotein (hnRNP) isoforms, most of which have been identified before in a previous study (14). The presence of these posttranslationally modified hnRNP peptides in serum/plasma has not been previously reported.…”
Section: Enrichment Workflow For Ptm Peptide Identification-tomentioning
confidence: 81%
“…following protocols described previously (14,15). Briefly, saturating amounts of the indicated antibodies were bound to 30 l packed Protein A agarose beads (Roche, Indianapolis, IN) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry-based proteomics is a well-established tool for the global identification of post-translational modification (PTM) sites and can be effectively coupled with immunoaffinity enrichment of peptides using "pan-specific" antibodies that bind to modified peptides independent of surrounding sequence context (19,20). Enrichment of modified peptides using panspecific antibodies has allowed for the identification of thousands of acetylated and ubiquitinated lysine sites in cells (21)(22)(23), and we and others have shown that pan-specific methyl-lysine or methyl-arginine antibodies can effectively and robustly enrich methylation modifications as well (7,8). Immunoaffinity enrichment is particularly critical in the case of methyl-lysine peptides, as the methyl moiety itself imparts sufficiently little physiochemical change to the side chain, rendering the enrichment of these peptides refractory to conventional separation methods.…”
mentioning
confidence: 99%
“…Protein lysine methyltransferases (PKMTs) 1 catalyze the sequence-specific transfer of one, two, or three methyl groups to the side chains of lysine residues (1-4). In addition to the extensively studied lysine methylation on histones, PKMTs can modify non-histone proteins (3,(5)(6)(7)(8)). An increasing number of non-histone proteins have been reported as PKMT substrates, and, as a result, potential roles for the dysregulation of non-histone lysine methylation in cancer development and progression have been proposed (9).…”
mentioning
confidence: 99%